Reconstructing Qur’anic Social Ethics: A Thematic Exegesis of Ta’awun and Its Implications for Social Assistance Governance in Indonesia: (Merekonstruksi Etika Sosial Al-Qur’an: Tafsir Tematik tentang Ta’awun dan Implikasinya bagi Tata Kelola Bantuan Sosial di Indonesia) - Fitri Meliani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
The governance of social assistance in Indonesia reflects a structural ethical crisis characterized by weak accountability, limited transparency, and the misuse of authority that disproportionately affects vulnerable groups. This condition indicates a significant gap between Qur’anic ethical values and contemporary social policy practices. This study aims to reconstruct the Qur’anic concept of ta‘awun as a framework of Qur’anic social ethics to analyze the misuse of social assistance in the Indonesian context. Employing a qualitative approach, this research applies a contextual thematic (maudhu’i) interpretation method integrated with Islamic social ethics, analyzing Qur’anic verses related to ta‘awun through Makkan–Madinan classification, semantic analysis, and thematic synthesis, supported by classical and contemporary Qur’anic commentaries as well as social policy literature. The findings demonstrate that ta‘awun encompasses three interrelated dimensions: a spiritual dimension as the foundation of the human God relationship, a social dimension emphasizing solidarity and collective responsibility, and a normative dimension defining ethical boundaries of cooperation. The principle of ta‘awun ‘ala al-birr wa al-taqwa embodies accountability, distributive justice, and transparency in social assistance governance, whereas the misuse of social assistance represents an institutional manifestation of ta‘awun ‘ala al-ithm wa al-‘udwan. This study concludes that reconstructing ta‘awun as a Qur’anic ethical framework provides a relevant normative foundation for strengthening ethical and accountable social assistance governance. The novelty of this research lies in integrating thematic Qur’anic interpretation with Islamic social ethics and contemporary governance discourse, positioning ta‘awun as an institutional ethical principle rather than merely an individual moral injunction.